2016
DOI: 10.1016/j.jlp.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of direct spring loaded pressure relief valves: III valves in liquid service

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractPrevious studies into direct-spring pressure relief valves connected to a tank via a straight pipe are adapted to take account of liquid sonic velocity. Good agreement is found between new experimental data and simulations of a coupled fluid-structure mathematical model. Upon increasing feed mass flow rate, there is a critical pipe length above which a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In Tamura et al (2012a) a standing quarter-wave was found numerically in the stub pipe of several relief valves during the oscillations. We also point to our previous work Hős et al (2014); Hős et al (2015); Hős et al (2016)) where, besides mathematical modelling, a large amount of experimental evidence was provided for the presence of quarter-wave instabilities in both liquid and gas service.…”
Section: Quarter-wave Instabilitymentioning
confidence: 58%
See 4 more Smart Citations
“…In Tamura et al (2012a) a standing quarter-wave was found numerically in the stub pipe of several relief valves during the oscillations. We also point to our previous work Hős et al (2014); Hős et al (2015); Hős et al (2016)) where, besides mathematical modelling, a large amount of experimental evidence was provided for the presence of quarter-wave instabilities in both liquid and gas service.…”
Section: Quarter-wave Instabilitymentioning
confidence: 58%
“…We found the above formula to be particularly accurate in the case of liquid service valves Hős et al (2016). If the valve is in gas service, the above formula can be still used provided that the gas properties (notably density and sonic velocity) are evaluated at set pressure.…”
Section: Quarter-wave Instabilitymentioning
confidence: 98%
See 3 more Smart Citations